ARTERIAL STIFFNESS IN END STAGE RENAL DISEASE PATIENTS WITH TWICE A WEEK HEMODIALYSIS AND ITS AFFECTING FACTORS - Nugroho, Pringgodigdo; Herdita, Tanya; Noor, Chairina Azkya; Putranto, Rudi; Rumende, Cleopas Martin (Journal of Postgraduate Medical Institute, 2021)
Objective: To investigate the proportion of arterial stiffness in patients on twice weekly maintenance hemodialysis and the factors affecting it. Methodology: This observational study with a cross-sectional design was performed in the Haemodialysis Unit, Kidney and Hypertension Division, Dr. Cipto Mangunkusumo National General Hospital, Jakarta, Indonesia. The study enrolled 83 End Stage Renal Disease (ESRD) patients undergoing hemodialysis two times a week for at least three months. Patients with acute disease were excluded from the study. Arterial stiffness was measured as pulse wave velocity (PWV) using SphygmoCor® with PWV cut-off of 10m/s. SPSS 21.0 was used as an analysis tool; descriptive and inferential statistics were applied where needed. Results: In the sample, 42 (50.6%) were male and 41 were female (49.4%). Among all participants, 22 (26.5%) patients were with arterial stiffness and 61 (73.5%) were without arterial stiffness. Factors independently affecting arterial stiffness were fasting glucose level (odds ratio 6.842 [CI95% 1.66-28.24]) and LDL level (odds ratio 4.887 [CI95% 1.59-16.58]). Conclusion: The proportion of arterial stiffness in ESRD patients undergoing hemodialysis two times a week was about one third of all patients. In factors affecting arterial stiffness among ESRD patients, fasting glucose level and LDL level were found to have higher odds.